A longitudinal study of cytochrome P450 2D6 (CYP2D6) activity during adolescence. Issue 10 (23rd August 2022) - Leeder, J. Steven; Gaedigk, Andrea; Wright, Krista J.; Staggs, Vincent S.; Soden, Sarah E.; Lin, Yvonne S.; Pearce, Robin E.
Abstract: CYP2D6 substrates are among the most highly prescribed medications in teenagers and also commonly associated with serious adverse events. To investigate the relative contributions of genetic variation, growth, and development on CYP2D6 activity during puberty, healthy children and adolescents 7–15 years of age at enrollment participated in a longitudinal phenotyping study involving administration of 0.3 mg/kg dextromethorphan (DM) and 4‐h urine collection every 6 months for 3 years (7 total visits). At each visit, height, weight, and sexual maturity were recorded, and CYP2D6 activity was determined as the urinary molar ratio of DM to its metabolite dextrorphan (DX). A total of 188 participants completed at least one visit, and 102 completed all seven study visits. Following univariate analysis, only CYP2D6 activity score ( p < 0.001), urinary pH ( p < 0.001), weight ( p = 0.018), and attention‐deficit/hyperactivity disorder (ADHD) diagnosis ( p < 0.001) were significantly correlated with log(DM/DX). Results of linear mixed model analysis with random intercept, random slope covariance structure revealed that CYP2D6 activity score had the strongest effect on log(DM/DX), with model‐estimated average log(DM/DX) being 3.8 SDs higher for poor metabolizers than for patients with activity score 3. A moderate effect on log(DM/DX) was observed for sex, and smaller effects were observed for ADHD diagnosis and urinary pH. The log(DM/DX) did not change meaningfully with age or pubertal development. CYP2D6 genotype remains the single, largest determinant of variability in CYP2D6 activity during puberty. Incorporation of genotype‐based dosing guidelines should be considered for CYP2D6 substrates given the prevalent use of these agents in this pediatric age group.